The a plus b whole square formula can be proved algebraically by the multiplication of algebraic expressions. It is actually derived in mathematics by multiplying a sum-based binomial with the same binomial and let’s learn how to derive the expansion of the a+b whole square algebraic identity in algebraic method.

Let’s denote two unknown quantities by two letters $a$ and $b$, their sum forms a binomial and it is written as $a+b$ in mathematics. Now, multiply the algebraic expression $a+b$ by itself and their product is expressed in mathematical form as follows.

$(a+b) \times (a+b)$

The product of the sum based two same binomials can be written in exponential notation as per the exponentiation.

$\implies$ $(a+b) \times (a+b)$ $\,=\,$ $(a+b)^2$

It is a special case in algebra. Hence, the product of two same sum basis binomials is often called as the special product of binomials or the special binomial product.

$\implies$ $(a+b)^2$ $\,=\,$ $(a+b) \times (a+b)$

The $a$ plus $b$ whole square represents the square of sum of two terms and it can be expanded by multiplying the algebraic expression $a+b$ with same binomial. Therefore, multiply the algebraic expressions by using multiplication of algebraic expressions.

$\implies$ $(a+b)^2$ $\,=\,$ $(a+b) \times (a+b)$

$\implies$ $(a+b)^2$ $\,=\,$ $a \times (a+b) +b \times (a+b)$

$\implies$ $(a+b)^2$ $\,=\,$ $a \times a + a \times b + b \times a + b \times b$

$\implies$ $(a+b)^2$ $\,=\,$ $a^2+ab+ba+b^2$

The square of sum of terms $a$ and $b$ is expanded as an algebraic expression $a^2+ab+ba+b^2$. According to commutative property, the product of $a$ and $b$ is equal to the product of $b$ and $a$. So, $ab = ba$.

$\implies$ $(a+b)^2$ $\,=\,$ $a^2+ab+ab+b^2$

Now, add the like algebraic terms in the algebraic expression by the addition of algebraic terms for simplifying the expansion of the $a$ plus $b$ whole square identity.

$\implies$ $(a+b)^2$ $\,=\,$ $a^2+2ab+b^2$

$\,\,\, \therefore \,\,\,\,\,\,$ $(a+b)^2$ $\,=\,$ $a^2+b^2+2ab$

Algebraically, it is proved that the $a$ plus $b$ whole square is equal to the $a$ squared plus $b$ squared plus two times product of $a$ and $b$. It is used as formula in mathematics to expand square of sum of two terms.

Latest Math Topics

Aug 31, 2024

Aug 07, 2024

Jul 24, 2024

Dec 13, 2023

Latest Math Problems

Sep 04, 2024

Jan 30, 2024

Oct 15, 2023

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved